Produção de sementes de soja enriquecidas com molibdênio - Oliveira, Carina Oliveira E (2017)
ABSTRACTThe objective was to evaluate the production of seeds enriched by the application of foliar molybdenum (Mo) doses and the growth and yield of plants resulting from the seeds obtained in this cultivation. We used the cultivar BRS Valiosa RR and in the first year, we used three doses of molybdenum (0, 400, and 800 g ha-1), with four replications. With the harvested seeds, three lots of seeds with different Mo contents were formed (9.27; 51.56, and 65.43 mg kg-1 of Mo). In the second year, using the seeds produced, two experiments were set, conducted in parallel. The first experiment was arranged in a randomized block design in a 3 × 3 scheme with four replications - three application methods (without application, at sowing, and foliar in the V4 stage at the dose of 25 g ha-1 Mo) and the three lots of seeds from the previous year. The second experiment was arranged in a randomized block design in a 4 × 4 × 3 scheme with four replications - four application stages (V4, in pre-flowering, in R3, and R5) × four foliar Mo doses (0, 25, 50, and 100 g ha-1) × three batches of seeds enriched with different Mo contents from the previous year. The protein content in seeds was 9% higher in the presence of Mo, regardless of how this was provided. The use of Mo is positive for soybean yield, when provided by the use of seeds enriched with a level of up to 51.56 mg kg-1 or by foliar application at doses between 25 and 50 g ha-1.